On The Strong Edge Monophonic Number of Graphs - Xavier, D. Antony; Infanta, Bino LG (International Journal of Computer Sciences and Engineering, 2025)
Abstract For a connected graph of order at least two, a set of vertices of is a Strong edge Monophonic set if every edge of is contained in a fixed monophonic path between any pair of vertices of . The minimum cardinality of the strong edge monophonic set is the strong edge monophonic number of denoted my . In this paper, certain general properties of the strong edge monophonic sets are studied. Also the strong monophonic number of some families of graph are determined